2021
DOI: 10.1136/bjsports-2021-104623
|View full text |Cite
|
Sign up to set email alerts
|

Bystander interventions and survival after exercise-related sudden cardiac arrest: a systematic review

Abstract: ObjectiveTo evaluate the provision of bystander interventions and rates of survival after exercise-related sudden cardiac arrest (SCA).DesignSystematic review.Data sourcesMEDLINE, EMBASE, PubMed, CINAHL, SPORTDiscus, Cochrane Library and grey literature sources were searched from inception to November/December 2020.Study eligibility criteriaObservational studies assessing a population of exercise-related SCA (out-of-hospital cardiac arrests that occurred during exercise or within 1 hour of cessation of activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 91 publications
0
8
0
3
Order By: Relevance
“…Exercise‐induced SCA is more likely to present with shockable rhythms such as VT or VF, making the use of an AED imperative for optimal outcomes. However, AED use remains suboptimal in this population 69,70 . For example, a prospective cohort study conducted in Germany and France found that an AED was utilized in only 7.5% of 147 cases of sports‐related SCA, despite those who received defibrillation having a survival rate of nearly 91% 70 .…”
Section: Limitations Of Cpr/aed Use: Bystander Initiationmentioning
confidence: 99%
“…Exercise‐induced SCA is more likely to present with shockable rhythms such as VT or VF, making the use of an AED imperative for optimal outcomes. However, AED use remains suboptimal in this population 69,70 . For example, a prospective cohort study conducted in Germany and France found that an AED was utilized in only 7.5% of 147 cases of sports‐related SCA, despite those who received defibrillation having a survival rate of nearly 91% 70 .…”
Section: Limitations Of Cpr/aed Use: Bystander Initiationmentioning
confidence: 99%
“…Na maioria dos casos descritos na literatura afirmam que a morte súbita se apresenta por meio de uma arritmia ventricular com ritmo chocável, o que justifica a relevância do uso imediato da desfibrilação (GRUBIC et al, 2022;DEFRODA et al, 2019;JONG et al, 2020). Nesse sentido, esse evento apesar de raro e dramático pode ser amenizado, por meio da adoção do tratamento adequado e de medidas preventivas, a fim de prevenir mortes e sequelas graves.…”
Section: Manejo Na Emergênciaunclassified
“…O resultado constatou que tanto a RCP do espectador bem como a utilização do DEA está em associação com as taxas de sobrevida após a parada cardíaca súbita vinculada ao exercício. No entanto, ressalta-se a necessidade de ampliação na promoção do conhecimento e na identificação precoce do evento, bem como da realização de uma ação ágil do espectador mediante a parada cardíaca súbita vinculada ao exercício (GRUBIC et al, 2022).…”
Section: Sobrevidaunclassified
“…During an exercise-related sudden cardiac arrest, bystander automated external defibrillator (AED) use occurred in a median of 31% (Grubic et al, 2021). Hence, increasing knowledge of and training in basic life support (BLS) and the use of defibrillators among the lay public would be expected to improve the survival and prognosis of out-of-hospital cardiac arrest (Ro et al, 2019;Vancini et al, 2019;Yu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%